What would be the correct translation of the terms "trigeminal nerve"? Let’s use "nervo trigêmeos" or "nervo trigeminal" - Valença, Marcelo Moraes (Headache Medicine, 2022)
What would be the correct translation of the terms "trigeminal nerve"? Let's use "nervo trigêmeos" or "nervo trigeminal"